Fenologia e mistura de reguladores vegetais e de fertilizante foliar no metabolismo da videira cv. sweet sunshine em clima semiárido - Souza, Essione Ribeiro [UNESP] (2014)
The aim of this study was to characterize the ‘Sweet Sunshine’ grapevine in “Vale do São Francisco” submedium, as well as evaluate the effects of plant growth regulators and foliar fertilizer on physiological and productive characteristics, and reducing the a fruitlet abscission index, in two periods, first and second semesters. Two experiments were performed both in the 2nd semester of 2012 and 1st semester of 2013, and another experiment with the mixture of plant growth regulators and foliar fertilizer only in the 1st semester of 2013. The first experiment was related to phenological characterization, for which were selected 12 plants, distributed in 4 blocks. The phenology of the cultivar was evaluated by visual observations performed weekly from pruning to harvest. The second experiment was related to the application of plant growth regulators (IBA+GA3+Kt) and foliar fertilizer (N, P2O5, S, Mo, Co): Control; plant growth regulators 1.6 L ha-1; plant growth regulators 1.8 L ha-1; plant growth regulators 2.0 L ha-1; Foliar Fertilizer 1.2 L ha-1 and foliar fertilizer 1.5 L ha-1. The treatments applications were carried out in separate flowers, 14 days after the first one and 14 days after the second application. The experiment, referring to a single application of the mixture of plant growth regulators combined with foliar fertilizer, in growing berries phase, presented the following treatments: Control; plant growth regulators 1.6 L ha-1 + foliar fertilizer 1.2 L ha-1; plant growth regulators 1.6 L ha-1 + foliar fertilizer 1.5 L ha-1; plant growth regulators 1.8 L ha-1 + foliar fertilizer 1.2 L ha-1; plant growth regulators 1.8 L ha-1 + foliar fertilizer 1.5 L ha-1. Data were subjected to analysis of covariance. The effects of the plant growth regulators...